The Influence of Islamic Advertising Ethics, Consumer Satisfaction, Brand Image on Online Purchasing Decisions - Dharmawan, Donny; Elizabeth, Elizabeth; Ekasari, Silvia; Dewi, Luh Komang Candra; Judijanto, Loso (International Journal of Artificial Intelligence Research, 2024)
The purpose of this research is to analyze the factors that can influenceonline purchasing decisions of Shopee application users. These factorsconsist of Islamic advertising ethnics, consumer satisfaction, brandimage. This research applies quantitative techniques and is analyzedusing IBM SPSS version 25. Sampling applies the purposive samplingmethod and the number of samples for this research is 110 respondentsobtained by distributing questionnaires to Shopee users in Surabayaonline via WhatsApp. The data was analyzed through several stages oftesting, namely validity testing, reliability testing, classical assumptiontesting, multiple linear regression analysis and determination coefficienttesting. The results of this research show that this study shows thatIslamic advertising ethnics, consumer satisfaction, have a positive andsignificant effect on online purchasing decisions, while brand imagedoes not have a significant effect on online purchasing decisions atShopee